Development of Microcontroller Arduino Atmega2560 Based Bluetooth Controlled Trash Can and Vacuum Cleaner Robot - Zainuddin, Zainuddin (Indonesian Journal of Fundamental Sciences, 2025)
Abstract. This study aims to develop a Bluetooth controlled trash and vacuum cleaner robot based on the Arduino ATmega2560 microcontroller and to discover the responses of users after using the tool. The type of this study is research and development (R&D) with an experimental development model. The types of data obtained in this study are qualitative data and quantitative data using data collection instruments in a form of a questionnaire. Data analysis techniques employed descriptive statistical analysis technique. The results of the tests that had been conducted by the Bluetooth module, it can be concluded that Bluetooth can be connected to the trash robot at an optimal distance of 35 meters in an open area without obstructions and an optimal distance of 20 meters in a closed room. The results of testing the tool in terms of the functionality factor by using the trial-and-error test method obtained responses from two expert validators that are suitable for field trials. The results of the usability factor test were obtained from the responses of 30 respondents who interacted with the tool, the percentage of achievement is 89% or very feasible so that the tool that had been developed receive a good response from users. Keywords: robot, trash can, vacuum cleaner, microcontroller